1999
DOI: 10.4141/a98-082
|View full text |Cite
|
Sign up to set email alerts
|

Effects of in vitro addition of ammonia on the metabolism of 15N-labelled amino acids in isolated sheep hepatocytes

Abstract: Chez les hépatocytes incubés en présence de 15 N alanine, la présence de NH 4 C1 n'avait pas d'effet sur l'accumulation de l'isotope dans l'urée à marquage simple (P = 0,705) ou double (P = 7,204), ni sur la production des deux formes d'urée (respectivement P = 0,279 et P = 0,708). Par ailleurs, l'apport de NH 4 C1 entraînait une augmentation de la production d'urée 14 N 15 N dans les substrats d'incubation contenant de la 15N méthionine (effet quadratique P = 0,019), mais n'avait pas d'effet dans les substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
2

Year Published

2001
2001
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 12 publications
1
8
2
Order By: Relevance
“…The data of Lobley et al (1995) demonstrated that an NH 3 load increased oxidation of Leu in sheep, although this response has been attributed to metabolic acidosis in response to NH 4 Cl infusion (Lobley et al, 1996). Our results also contrast the data of Mutsvangwa et al (1999), in which Met deamination was increased with NH 3 loading in vitro.…”
Section: Resultscontrasting
confidence: 81%
See 2 more Smart Citations
“…The data of Lobley et al (1995) demonstrated that an NH 3 load increased oxidation of Leu in sheep, although this response has been attributed to metabolic acidosis in response to NH 4 Cl infusion (Lobley et al, 1996). Our results also contrast the data of Mutsvangwa et al (1999), in which Met deamination was increased with NH 3 loading in vitro.…”
Section: Resultscontrasting
confidence: 81%
“…The use of AA N in ureagenesis may affect the use of AA for protein synthesis. In fact, NH 3 loading increased oxidation of Leu in vivo (Lobley et al, 1995) and Met and Ala in vitro (Mutsvangwa et al, 1996(Mutsvangwa et al, , 1999.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they have shown that 5-d duodenal ammonia infusions in Holstein-Friesian dairy cows did not significantly change milk yield or milk constituent yields. In vitro studies by Mutsvangwa et al (1999) using isolated sheep hepatocytes and 15 N-labelled amino acids (met, leu, phe) provided evidence that NH 3 detoxification to urea stimulates methionine catabolism, but that leucine and phenylalanine catabolism were not affected. This could imply that in cows experiencing a deficiency in methionine, ammonia detoxification could put a stress on the requirement for methionine and, subsequently, reduce milk yield and/or milk protein.…”
Section: Resultsmentioning
confidence: 99%
“…In vivo (Lobley et al, 1995) and in vitro (Mutsvangwa et al, 1996(Mutsvangwa et al, , 1999 studies suggested that metabolic ammonia (NH 3 ) loading might lead to inefficient use of dietary AA by metabolically consuming AA to provide α-amino N to support ureagenesis. We recently observed no negative effects of NH 3 loading on protein deposition when Met, Leu, or His limited cattle performance (Awawdeh et al, 2004(Awawdeh et al, , 2005McCuistion et al, 2004).…”
Section: Introductionmentioning
confidence: 99%